Density and stomata distribution in cassava Manihot esculenta Crantz IAC 576-70 - Carlos de Oliveira, Elio (2014)
In cassava the variation in stomata characteristics, such as density, polar diameter and functionality undergo changes due to the stomata frequency distributed in different regions of the leaf blade. This study aimed to determine the density, diameters and distribution of stomata in different regions of cassava leaf. We analyzed the apices, median and basal expanded leaves of IAC 576-70. The experimental design was completely randomized with three regions sampled twenty replications, each leaf region observed in five microscopic fields. Data were subjected to analysis of variance and the averages compared by Tukey test. We evaluated data on the number, polar and equatorial diameter of the stomata and calculations of stomata density and functionality. There is no difference between stomata density, equatorial diameter and functionality of stomata in different regions of cassava leaf cultivar IAC 576-70, while the polar diameter of the stomata is smaller in the apical and median regions of leaves.